2017
DOI: 10.5430/jha.v6n6p42
|View full text |Cite
|
Sign up to set email alerts
|

The role and value of nurses in care provision: Views and expectations of Emirati Nationals in the western region of Abu Dhabi, United Arab Emirates

Abstract: Background: Reliable health user information is needed to effectively organize nursing services and deliver quality patientcentered care. Nurse leaders of Al Gharbia Health Services (AGHS) noted that although budget data and general workforce information were readily available, detailed information about patient experiences, views, and expectations was lacking. Objective: This study aimed to obtain preliminary data regarding health and nursing service expectations of Emirati nationals in the remote western reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Such Western views did mirror the Oceania study, where NZ nurses reported their perception of a “tick‐box mentality” in IQNs (e.g., 024). As Brownie, Rossiter, Hamad, and Aqtash () pointed out, sometimes the role of nursing as a science can supersede the art of caring, which to some nurses was a clear compromise to quality care. However, this task‐oriented focus may relate to significant cultural and organisational differences in the role of registered nurses in some countries, with nurses overseeing clinical interventions for a large patient group and family members providing all fundamental cares (Tregunno, Peters, Campbell, & Gordon, ; Tuttas, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such Western views did mirror the Oceania study, where NZ nurses reported their perception of a “tick‐box mentality” in IQNs (e.g., 024). As Brownie, Rossiter, Hamad, and Aqtash () pointed out, sometimes the role of nursing as a science can supersede the art of caring, which to some nurses was a clear compromise to quality care. However, this task‐oriented focus may relate to significant cultural and organisational differences in the role of registered nurses in some countries, with nurses overseeing clinical interventions for a large patient group and family members providing all fundamental cares (Tregunno, Peters, Campbell, & Gordon, ; Tuttas, ).…”
Section: Resultsmentioning
confidence: 99%
“…As Brownie, Rossiter, Hamad, and Aqtash (2017) pointed out, sometimes the role of nursing as a science can supersede the art of caring, which to some nurses was a clear compromise to quality care.…”
Section: Theme 4: Challenges To Professionalismmentioning
confidence: 99%
“…Over the last decade, undergraduate nursing education in the UAE has progressed to align with the UAE vision for quality healthcare and graduate nurses with baccalaureate qualifications to meet the demand for knowledgeable nursing professionals (Brownie et al, 2015). These programmes were challenged by the poor local image of nursing as a profession, although this perception is improving (Brownie et al, 2017). Other challenges included the slow development and adoption of international advances, the limited number of nursing faculty members in advanced specialized practice and the quality of clinical practice sites being inadequate to meet students' learning needs (Al‐Yateem et al, 2020a, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…producing competent nurses who can practise globally) (Mckinnon, Mcnelis, Leon, Whitlow, & Fitzpatrick, 2019; Mcnelis & Mckinnon, 2019; Palmer & Miles, 2019) and the role of technology in education (Broadbent, 2017; Thomas, West, & Borup, 2017). UAE‐based discussions regarding these aspects are still in the early stages, and they remain to be achieved in nursing education (Al‐Yateem et al, 2019; Brownie, Hunter, Aqtash, & Day, 2015; Brownie, Rossiter, Hamad, & Aqtash, 2017; El‐Haddad, 2006; Gomez, 2010; Johnson, 1992; Kronfol & Athique, 1986; McCreaddie et al, 2018; Nematollahi & Isaac, 2012; Torres‐Alzate, 2019). This suggests the road map for the UAE nursing education system needs to be strengthened.…”
Section: Nursing Leadership and Management Challengesmentioning
confidence: 99%
“…A major contributor to this low admission rate was the poor local image of nursing and hesitation to regard nursing as an education and career option. However, there is growing evidence that this perception is changing (Brownie et al, 2017; El‐Haddad, 2006).…”
Section: Nursing Leadership and Management Challengesmentioning
confidence: 99%